2020
DOI: 10.1158/0008-5472.can-20-0078
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Epigenomic Landscaping Defines New Therapeutic Targets for Adenosquamous Carcinoma of the Pancreas

Abstract: Adenosquamous cancer of the pancreas (ASCP) is a subtype of pancreatic cancer that has a worse prognosis and greater metastatic potential than the more common pancreatic ductal adenocarcinoma (PDAC) subtype. To distinguish the genomic landscape of ASCP and identify actionable targets for this lethal cancer, we applied DNA content flow cytometry to a series of 15 tumor samples including five patient-derived xenografts (PDX). We interrogated purified sorted tumor fractions from these samples with whole-genome co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 45 publications
5
41
0
Order By: Relevance
“…Consistent with a previous report (Cancer Genome Atlas Research Network, 2017), some of these molecular classifications overlapped significantly, such as ''ADEX'' (Bailey) and ''exocrine-like'' (Collisson), ''Classical (Collisson)'' and ''pancreatic progenitor'' (Bailey), and ''squamous'' (Bailey), ''quasimesenchymal'' (Collisson) and ''basal-like'' (Moffitt) (p < 0.0001, Fisher's exact test). Notably, five adenosquamous carcinoma samples in our cohort were classified into ''squamous'' (Bailey), ''quasimesenchymal'' (Collisson), or ''basal-like'' (Moffit) groups, in line with the understanding for this histological pancreatic cancer subtype (Boecker et al, 2020;Lenkiewicz et al, 2020;Moffitt et al, 2015). Non-negative matrix factorization (NMF)-based proteogenomics subtyping using multiomics data from all 140 tumors revealed four clusters with significant overlap with RNA subtypes (Figures S7B and S7C; Table S7A).…”
Section: Proteogenomic Subtypes With Strong Prognostic Relevancementioning
confidence: 90%
“…Consistent with a previous report (Cancer Genome Atlas Research Network, 2017), some of these molecular classifications overlapped significantly, such as ''ADEX'' (Bailey) and ''exocrine-like'' (Collisson), ''Classical (Collisson)'' and ''pancreatic progenitor'' (Bailey), and ''squamous'' (Bailey), ''quasimesenchymal'' (Collisson) and ''basal-like'' (Moffitt) (p < 0.0001, Fisher's exact test). Notably, five adenosquamous carcinoma samples in our cohort were classified into ''squamous'' (Bailey), ''quasimesenchymal'' (Collisson), or ''basal-like'' (Moffit) groups, in line with the understanding for this histological pancreatic cancer subtype (Boecker et al, 2020;Lenkiewicz et al, 2020;Moffitt et al, 2015). Non-negative matrix factorization (NMF)-based proteogenomics subtyping using multiomics data from all 140 tumors revealed four clusters with significant overlap with RNA subtypes (Figures S7B and S7C; Table S7A).…”
Section: Proteogenomic Subtypes With Strong Prognostic Relevancementioning
confidence: 90%
“…In particular, mutations in the histone-lysine N-methyltransferase 2 (KMT2)C and KMT2D, the ATP-dependent chromatin remodeler SMARCA4, and lysine demethylase (KDM)6 are reported in 7%, 5%, and 5% of the patients, respectively [85]. A recent manuscript by Lenkiewicz and collaborators showed mutations also in the KDM3 [86]. Alongside confirming the alterations in chromatin regulatory genes, this manuscript is very relevant for two critical aspects: (I) it confirms that ASC evolves from the same lineage as PDAC, as they share canonical mutations in KRAS, TP53, CDKN2A, SMAD4 and MYC; and (II) it demonstrates that the genetic characterization of the PDAC variants is crucial in defining new therapeutic intervention strategies.…”
Section: Adenosquamous Carcinomamentioning
confidence: 99%
“…By ATAC-seq in KPC mouse model, the authors define the status of the nuclear receptor ROR-γ (RORC)-a nuclear receptor hormone involved in the Th-17-dependent inflammatory cytokines release-as a specific feature of ASC; the authors also demonstrated the co-occurrence of genetic alterations in KRAS and fibroblast growth factor receptor (FGFR). From an interesting translational point of view, the authors showed that organoids RORC + /FGFR-ERLIN2 fusion/KRAS G12V are more sensitive to the single-agent FGFR inhibitor infigratinib [86].…”
Section: Adenosquamous Carcinomamentioning
confidence: 99%
“…However, within the exocrine pancreas, multiple other forms of malignancies can occur. This includes adenosquamous carcinoma of pancreas (ASCP), an aggressive sub-type of PDAC that has the worst clinical prognosis [4][5][6] ; acinar cell carcinoma (ACC), which accounts for 15% of all childhood pancreatic cancers and is only moderately responsive to chemotherapies 7 ; and the highly aggressive anaplastic tumors, characterized by their undifferentiated state 8 . While originally considered rare, recent studies have indicated that a substantially higher fraction of conventional PDAC (18%) harbors admixed adenosquamous features than was previously recognized 9 .…”
mentioning
confidence: 99%
“…Here we report a new mouse model in which targeting oncogenic Myc to adult pancreatic precursor cells triggered the development of PDAC, ASCP, ACC and anaplastic tumors. Our current model is particularly exciting and highly relevant to human disease, as deregulated expression or amplification of c-MYC is associated with higher incidence of ASCP (47%) and ACCs (54% in pure and up to 100% in mixed ACCs) in human pancreatic patients, irrespective of KRAS mutation status 5,15,16 . This work provides an exciting new model for multiple subtypes of pancreatic cancer, and a unique opportunity to trace, at single cell resolution, the origins of the pre-malignant state and its evolution to distinct lethal malignancies.…”
mentioning
confidence: 99%